An Appraisal of the Role of the Permanent Court of Arbitration in Dispute Resolution - Otu, Mike; Mabiebu, Miebaka; Njong, Cleverty Afu; Etiowo, Obaseopuwhoi Mbang (dialektika kontemporer, 2024)
The Permanent Court of Arbitration (PCA) is a unique international organisation, particularly in the dispute resolution spectrum. Its uniqueness stems from the mere fact that it is not a court in the true sense of the word. Interestingly, this unique international organisation has played a vital role in dispute resolution, particularly in international arbitration, and has not relented for over a hundred (100) years. Despite its role, it is regrettably unfortunate that the PCA remains an unsung hero. Adopting an expository method of research, this article gives us an insight into the role of the Permanent Court of Arbitration in the resolution of disputes.